2013
DOI: 10.2337/dc12-0658
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Free-Living Interval-Walking Training on Glycemic Control, Body Composition, and Physical Fitness in Type 2 Diabetic Patients

Abstract: OBJECTIVETo evaluate the feasibility of free-living walking training in type 2 diabetic patients and to investigate the effects of interval-walking training versus continuous-walking training upon physical fitness, body composition, and glycemic control.RESEARCH DESIGN AND METHODSSubjects with type 2 diabetes were randomized to a control (n = 8), continuous-walking (n = 12), or interval-walking group (n = 12). Training groups were prescribed five sessions per week (60 min/session) and were controlled with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
364
6
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(394 citation statements)
references
References 39 publications
9
364
6
15
Order By: Relevance
“…Since five individuals initially randomised to the CON group were re-randomised to either IWT or CWT after the CON period, the final study population consisted of n=27 individuals with n=32 pre-/post-intervention trial participants included for statistical analysis (CON, n=8; CWT, n=12; IWT, n=12). The randomisation procedure and the body composition, physical fitness and glycaemic control data have been reported in full elsewhere [6]. Written informed consent was obtained from all individuals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since five individuals initially randomised to the CON group were re-randomised to either IWT or CWT after the CON period, the final study population consisted of n=27 individuals with n=32 pre-/post-intervention trial participants included for statistical analysis (CON, n=8; CWT, n=12; IWT, n=12). The randomisation procedure and the body composition, physical fitness and glycaemic control data have been reported in full elsewhere [6]. Written informed consent was obtained from all individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all training sessions were performed with a heart rate monitor (Polar RS400; Polar, Kempele, Finland). The training protocol has been described in detail elsewhere [6]. Briefly, CWT consisted of continuous walking at individualised moderate intensity (≥55% of the individual's peak energy expenditure rate for walking [V ⋅ O 2peak ]), whereas IWT consisted of alternating 3 min intervals of fast (≥70% of V ⋅ O 2peak ) and slow (~40% of V ⋅ O 2peak ) walking.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, exercise helps to normalise plasma glucose [23] and serum lipids [24] in individuals with, or at risk of, diabetes. These factors when chronically elevated are known to cause beta cell death.…”
Section: Search Strategymentioning
confidence: 99%
“…Accordingly, the effect of different intensities and types of physical activity may have different effects on glucose metabolism. This has mainly been investigated in low risk populations, and the findings are equivocal [14][15][16][17][18]. Furthermore, studies have found that CRF changes the direction and/or strength of the association between PAEE and cardiometabolic risk factors [19,20], suggesting that the beneficial effect of PAEE is dependent on the intensity of the activities contributing to PAEE.…”
Section: Introductionmentioning
confidence: 99%